A brief overview of current approaches for underwater sound analysis and reporting. (May 2022) - van Geel, Nienke C.F.; Risch, Denise; Wittich, Anja
Abstract: Soundscapes have substantially changed since the industrial revolution and in response to biodiversity loss and climate change. Human activities such as shipping, resource exploration and offshore construction alter natural ecosystems through sound, which can impact marine species in complex ways. The study of underwater sound is multi-disciplinary, spanning the fields of acoustics, physics, animal physiology and behaviour to marine ecology and conservation. These different backgrounds have led to the use of various disparate terms, metrics, and summary statistics, which can hamper comparisons between studies. Different types of equipment, analytical pathways, and reporting can lead to different results for the same sound source, with implications for impact assessments. For meaningful comparisons and derivation of appropriate thresholds, mitigation, and management approaches, it is necessary to develop common standards. This paper presents a brief overview of acoustic metrics, analysis approaches and reporting standards used in the context of long-term monitoring of soundscapes. Highlights: Human activities alter marine soundscapes, impacting species in complex ways. Underwater sound studies require collaboration across disciplines using common standards. We summarise approaches to underwater sound analysis, reporting, and management.